A trompa e a música brasileira popular na Escola de Música da Universidade Federal do Rio Grande do Norte - Cunha, André Rodrigues de Lima da (2018)
Research about instrumental practices and instrumental teaching has expanded in recent years. As part of this process it is included the application of new approaches of teaching in the academic music universe. It is possible to observe that popular music, in its broad sense, plays an important role in this context, as evidenced in the practice and teaching of the Horn. This thesis problematizes Brazilian popular music as a tool for instrumental teaching and practices of Horn students of the Federal University of Rio Grande do Norte - UFRN. The main objective of this research is to verify the insertion of Brazilian popular music in the Horn Bachelor's degree course of UFRN and to identify perspectives and directions of these practices. The methodology included bibliographic research, documentary research, questionnaire, interview with the students and the Horn teacher of UFRN, as well as empirical experiments based on the performance of this professor. it was possible to observe that Brazilian popular music is contemplated in an effective way and the technical-interpretative aspects of this type of repertoire are studied from materials adapted from other instruments, also counting on the experience of the teacher interviewed and traditional methods for Horn. From the information collected it was possible to conclude that this approach is a possibility to expand the interpretative, technical and formative range of the student.